Penerapan Model PBL Berpendekatan Teaching at the Right Level (TaRL) Terhadap Hasil Belajar Kognitif Siswa SMKN 7 Semarang - Jumadin Jumadin; Supandi Supandi (FKIP Universitas Khairun, 2024)
The research is classroom action research which aims to improve students' mathematics learning outcomes through the application of the PBL model with the TaRL approach. The research subjects were 36 students of class X TE 3. The instruments used were observation sheets and learning outcomes tests. Data collection methods include information on student activities, implementation of actions, and student learning achievements. Student activity data will be interpreted qualitatively, while learning outcome data will be analyzed quantitatively through a descriptive statistical approach. From the research results, it was concluded that using the PBL model with the TaRL approach can improve students' mathematics learning outcomes.